2021
DOI: 10.2147/ijgm.s304007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Health Literacy in Patients with Cardiovascular Diseases: Cross-Sectional Study in Ethiopia

Abstract: This study assessed functional health literacy and associated factors among adult patients with cardiovascular diseases (CVDs) in Ethiopia. Methods: A cross-sectional study was conducted on 410 respondents from May 1 to July 1, 2020, using a functional health literacy questionnaire consisting of 14 items that covers three conceptually distinct functional health literacy domains: having sufficient information to manage my health, ability to find good health information and understand health information well eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…In this study, more than half of the participants had high health literacy. These findings were similar to a study done in Jimma Medical Center, Ethiopia; 19 , 27 even though the patients on follow up may be enhanced health literacy with the health education provided from the health care provider about their treatments. Where as in this study the level of health literacy may be increased due to the information they may get during their stay in hospital.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, more than half of the participants had high health literacy. These findings were similar to a study done in Jimma Medical Center, Ethiopia; 19 , 27 even though the patients on follow up may be enhanced health literacy with the health education provided from the health care provider about their treatments. Where as in this study the level of health literacy may be increased due to the information they may get during their stay in hospital.…”
Section: Discussionsupporting
confidence: 87%
“…Two studies, 32 and, 33 assessed functional HL (FHL) and communicative HL (CHL) respectively. Tilahun, Gezahegn, Tegenu, Fenta 32 measured FHL among adult patients with cardiovascular diseases using FHL scale adopted from the comprehensive HL Questionnaire (HLQ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, 32 and, 33 assessed functional HL (FHL) and communicative HL (CHL) respectively. Tilahun, Gezahegn, Tegenu, Fenta 32 measured FHL among adult patients with cardiovascular diseases using FHL scale adopted from the comprehensive HL Questionnaire (HLQ). 55 The FHL scale consists of 14 items covering three conceptually distinct domains of the comprehensive HLQ: having sufficient information (four items), finding good health information (five items), and understanding health information (five items).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have shown that health competence is insufficient in medically vulnerable groups, especially in individuals with epilepsy 18,19 , studies on health competence in individuals with epilepsy have been limited. 20,21 On the other hand, health competence affects disaster preparedness in individuals with epilepsy has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%